Optimizing Mental Health Cadres In Disaster Response: Stress Management and Spiritual Emotional Freedom Technique (SEFT) in Agricultural Communities - Rahmawati, Primasari Mahardhika; Rondhianto, Rondhianto; Pebriyanti, Dwi Ochta; Suhari, Suhari; Sulistyono, R Endro (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Natural disasters produce both immediate and prolonged psychological consequences, including stress, anxiety, and depression. These effects require comprehensive interventions combining stress management strategies with the Spiritual Emotional Freedom Technique (SEFT). This study aimed to enhance mental health cadres' capacity to support disaster resilience programs in agricultural communities, focusing on Indonesia's disaster-prone Lumajang District. The research implemented a two-phase intervention: First, 30 health cadres received training using a quantitative pre-experimental design with pre-test and post-test evaluations. Second, these trained cadres conducted home visits for 80 community members, with outcomes measured using the PTSD Checklist (PCL-5). Results demonstrated significant improvements across both cadres and community members. Cadres' stress management knowledge increased substantially from an average pre-test score of 50% (poor category) to 76.6% (good category) post-intervention. Most importantly, SEFT implementation reduced PTSD symptoms among community members from 41.25% to 11.25%. The study also revealed high participant engagement, with all 30 cadres completing training and demonstrating strong knowledge retention. These findings confirm that targeted training in SEFT and stress management can effectively enhance mental health cadres' professional capabilities. By strengthening frontline responders' skills, communities gain greater capacity to address post-disaster psychosocial challenges and build long-term resilience. The research highlights the value of integrating evidence-based psychological interventions with community health worker programs, particularly in vulnerable agricultural regions facing recurrent disasters. This cadre-centered approach offers a sustainable model for improving mental health outcomes in disaster-affected populations while supporting broader disaster preparedness initiatives. Where it will also support the achievement of SDG 3.